2005
DOI: 10.1038/nmeth759
|View full text |Cite
|
Sign up to set email alerts
|

Activity probe for in vivo profiling of the specificity of proteasome inhibitor bortezomib

Abstract: Proteasome inhibitors, such as the dipeptide boronic acid bortezomib, are emerging as important tools in the treatment of the fatal hematologic malignancy multiple myeloma. Despite the recent US Food and Drug Administration approval of bortezomib (PS341, Velcade) for the treatment of refractory multiple myeloma, many of the basic pharmacologic parameters of bortezomib and its mode of action on myeloma cells remain to be determined. We describe the synthesis and use of a cell-permeant active site-directed probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
223
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(238 citation statements)
references
References 21 publications
12
223
2
1
Order By: Relevance
“…Our data suggest that both NPI-0052 and Bortezomib differentially affect constitutive and immunoproteasome in MM.1S MM cell line (Chauhan et al, 2005a). A novel methodology was applied to measure proteasome activity by Western blot analysis using dansyl-Ahx 3 L 3 VS as a probe (Berkers et al, 2005). NPI-0052 inhibits b-5i, b-2i, and b-1i activities in MM cells.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Our data suggest that both NPI-0052 and Bortezomib differentially affect constitutive and immunoproteasome in MM.1S MM cell line (Chauhan et al, 2005a). A novel methodology was applied to measure proteasome activity by Western blot analysis using dansyl-Ahx 3 L 3 VS as a probe (Berkers et al, 2005). NPI-0052 inhibits b-5i, b-2i, and b-1i activities in MM cells.…”
mentioning
confidence: 89%
“…A further confirmation of the ability of NPI-0052 to block proteasomal activity was derived from experiments using a novel methodology (instead of conventional use of flourogenic substrate) to assess proteasome activity in MM cells. Specifically, competition experiments between NPI-0052 and a cell-permeable proteasome inhibitor dansylAhx 3 L 3 VS that covalently modifies all active proteasome subunits showed that NPI-0052 at the IC 50 doses for MM cells reduced the dansylAhx 3 L 3 VS-labelling of the b-5 (represents CT-L activity), b-1 (represents C-L activity), and b-2 (represents T-L activity) subunits (Berkers et al, 2005). Higher doses of Bortezomib are required to inhibit CT-L and C-L activity, whereas little, if any, inhibition of T-L activity was noted.…”
mentioning
confidence: 99%
“…The proteasome-specific affinity probe DALVS was synthesized as described [40]. Both the constitutive [b1, b2, b5)] and the immunoproteasome subunits (b1i, b2i, b5i) were labeled by DALVS in intact cells, which were incubated with 1 mM DALVS in complete medium at 371C for 1 h. Afterwards, cells were washed with 0.9% NaCl and lysed in 1% Triton X-100 on ice for 30 min followed by the removal of debris and membrane fractions by centrifugation.…”
Section: Affinity Labeling Of Active Proteasomesmentioning
confidence: 99%
“…Proteasome-directed ABPs have been used to evaluate the specificity of bortezomib, a clinically approved proteasome inhibitor for the treatment of multiple myeloma [37,38]. Myeloma cells were cultured in the presence or absence of bortezomib, incubated with a cell-permeable, proteasome-specific ABP, lysed, and then analyzed by gel electrophoresis.…”
Section: Enzyme Inhibitor Discovery and Verificationmentioning
confidence: 99%
“…Myeloma cells were cultured in the presence or absence of bortezomib, incubated with a cell-permeable, proteasome-specific ABP, lysed, and then analyzed by gel electrophoresis. Results from these experiments revealed that only the activities of the β1/β1i and β5/β5i subunits of the proteasome were inhibited by bortezomib [37,38]. The cancer drug, paclitaxel, used to treat breast and ovarian cancers, has also been tested for its efficacy in a cell-based assay using a wortmannin-containing ABP that targets polo-like kinase 1 (PLK1), an enzyme with highly elevated activity in the M phase of the cell cycle [39].…”
Section: Enzyme Inhibitor Discovery and Verificationmentioning
confidence: 99%